Up-regulating Sexual Arousal and Down-regulating Disgust while Watching Pornography: Effects on Sexual Arousal and Disgust. Issue 3 (24th March 2021) - Pawłowska, Aleksandra; Borg, Charmaine; de Jong, Peter J.
ABSTRACT: Sexual response occurs when sexual excitatory factors outweigh inhibitory factors. Problems with sexual arousal may occur when sexual excitation is too low and/or inhibitory influences such as feelings of disgust are too strong. To explore interventions that may help overcome decreased sexual responding, we examined if sexual responding could be amplified by instructions to up-regulate sexual arousal and/or down-regulate disgust. Women with no sexual difficulties (N = 255; µage  = 20.55; SD  = 2.23) were randomly assigned to a sexual arousal up-regulation, disgust down-regulation, or passive control condition. Participants were instructed to use the assigned regulation strategy while viewing pornography. To prevent floor effects due to low disgust responsivity in a non-clinical sample, half of the participants were presented with a prime that was designed to make the contaminating properties of sex more salient. Instruction to up-regulate sexual arousal successfully enhanced feelings of sexual arousal in the unprimed group, yet the increase in sexual arousal was not paralleled by reductions in feelings of disgust. Instruction to down-regulate disgust successfully decreased disgust; however, this decrease was not paralleled by increases in sexual arousal. Overall, findings indicate that emotion regulation techniques could facilitate affective control in sexual contexts.